ANALYSIS OF DISCUSSION DISCUSSION ON LIBERATION OF BA'ASYIR FUEL ASH ON ONLINE MEDIA - Mochamad Supriyadi (JLER (Journal of Language Education Research), 2020)
The character's life is always interesting to broadcast and of course, many people are interested and constructed to produce interesting news and broadcast on the media, including online media. The research method for analyzing the construction of celebrity news is a method of discourse analysis from Fairclough. This Fairclough discourse analysis is used to see more broadly the other side of the news so that there is no perception from one party only. Through critical discourse analysis, it is possible to find findings of the ideology of a variety of media available. The results of the study show that based on Fairclough's discourse analysis, there are differences in the content of news coverage in 2 online media. Each media frames the same news with a different frame according to the idealism of the media.